Analytical Study on the Application of Islamic Economic Law Principles at SPM Sharia Bank (Sarana Prima Mandiri), Pejagan–Bangkalan - Dea Yusiana (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2025)
Islamic Economic Law represents a set of norms and regulations governing commercial and non-commercial economic activities based on Islamic principles, either derived directly from the Qur’an and Sunnah or through human interpretation (ijtihad). Law No. 3 of 2006, Article 49, concerning the Religious Court, affirms that Sharia-based economic practices include institutions such as Islamic banks. This study aims to (1) analyze the implementation of Islamic Economic Law within the financial operations of the Sharia Bank SPM (Sarana Prima Mandiri), located at Jl. Trunojoyo 56, Pejagan, Bangkalan, and (2) identify the challenges and propose potential solutions to improve Sharia compliance and operational effectiveness. A qualitative descriptive approach was employed. The study used a single-variable framework focusing on implementation within BPRS SPM. Primary data were collected through interviews with the management and staff of PT. BPRS Sarana Prima Mandiri, while secondary data were obtained from institutional documents, brochures, and organizational profiles. The sampling technique used was simple random sampling with 20 employees selected as respondents. Data collection methods included observation, interviews, and documentation. The analysis was conducted using deductive and comparative techniques. The findings indicate that the implementation of Islamic Economic Law at BPRS SPM provides significant benefits for both the institution and its clients by enhancing awareness of Sharia-compliant financial practices. Additionally, it serves as a valuable reference for comparative evaluation and future strategic development. Strengthening the application of Islamic economic principles in financial institutions requires continuous education, improved governance, and adaptive strategies to overcome operational and regulatory challenges.